Innovation within Small-Medium Scale Contractors in Indonesia - Rizal Bahaswan; Zulaicha Parastuty; Ani Wulandari; Sri Wiwoho Mudjanarko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
In order to survive within the industry, small-medium scale contractors are required to be adaptive. However, many obstacles have been experienced by this group to deal with. The term of survive can be interpreted by doing continuous innovation. This research was conducted to investigate the innovation issues related which possibly could triggering or canceling the innovation within small-medium scale contractors. Literature study was conducted as a primary and followed by a field research using questioners. From the research it was found that the main motivation and orientation within innovation processes was the competitiveness among the group of contractors and followed by the attempt to respond the recently industry environment. However, they tend to avoid the change in their business concept. Finally, the availability in source of funding was highlighted as the main factor which might brough innovation initiative successful.